Ise Oluwa (God's work will never be destroyed) : Nigerian Chant - Kean, Ron; Bakersfield College Chamber Singers (California) ([Estados Unidos de América] : Pavane Publishing, 1998)
Resumen: Se presenta una breve interpretación de la canción Ise Oluwa por parte del grupo de coro de Bakersfield College Chamber Singers
"Instructional Video"--Otro título del envase: Ise Oluwa (God's work will never be destroyed): Nigerian folk song (Yoruba)
Interpretada por Bakersfield College Chamber Singers ; director, Ronald Kean
Keywords: MUSICA VOCAL; MUSICA CORAL; CANCIONES